Seroprevalence, clinical profile and knowledge, attitudes, and practices (KAPs) of brucellosis in North India in patients with pyrexia of unknown origin and chronic joint pain - Mittal, Charul; Sami, Hiba; Gururaj, K; Khan, Fatima; Sultan, Asfia; Khan, Haris M; Rizvi, Meher (International Journal of Human and Health Sciences (IJHHS), 2022)
Introduction: Brucellosis is a significant but lesser-known cause of pyrexia of unknown origin (PUO) in India. Studies documenting the prevalence of Brucellosis in different parts of India are sparse and few. Clinicians thus usually don’t consider it in their differential diagnosis. This study assesses its prevalence in two groups: febrile patients with unknown etiology and individuals presenting with arthritis and/or joint pains. Knowledge, Attitude, and Practices (KAP) among clinicians about the disease was evaluated. Materials and Methods: This is a prospective study conducted at a tertiary care center of North India catering to urban, semi-urban, and rural populace. Ninety-two patients with fever of unknown origin, arthralgia, or similar constitutional symptoms were recruited in this study. Detailed clinical history was elicited from all patients as per predesigned proforma and a rigorous physical examination was conducted. Following primary screening to rule out malaria, enteric fever, and leptospirosis, secondary screening for Brucellosis was done by Rapid Screen Test (PUO screen) and IgM and IgG ELISA. A predesigned survey was used for assessing KAP among clinicians about Brucellosis. Results: Brucella infection was diagnosed in 27 (29.3%) cases. The most common symptoms among the patients apart from fever were arthralgia (77.8%), fatigue (70.8%), pallor (66.1%), headache (59.2%), backache (53.8%) and cough (33.3%). PUO screen is a specific test for brucellosis but lacks sensitivity. It detects acute cases but misses chronic cases. IgM ELISA being more sensitive should be used for confirmation. Low ODs point to chronic brucellosis which was confirmed by IgG ELISA. Normal CRP levels in patients with PUO and chronic joint pains should point to brucellosis. KAP revealed that 25% to 50% of doctors considered Brucella in their differential diagnosis of acute and chronic fever respectively while 10% Orthopedics considered it in cases of arthralgia. Conclusion: Our results highlight the significance of Brucella as a cause of PUO and arthralgia. Brucellosis is an underrecognized but important cause of pyrexia of unknown origin and chronic joint pain. It should be actively suspected, diagnosed, and treated. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 80-88